1952
DOI: 10.1677/joe.0.0080196
|View full text |Cite
|
Sign up to set email alerts
|

Some Observations on the Kober Colour and Fluorescence Reactions of the Natural Oestrogens

Abstract: The two-stage Kober reaction with oestriol, oestrone and oestradiol-17\g=b\ has been investigated. The factors involved in the maximum production of colour are summarized.Reducing agents were important in both the first and second stages of the Kober reaction. Oestriol in small amounts did not form the red Kober colour when reducing agents were not present in the first stage.In the absence of water, sulphuric acid did not give optimal results in the first stage. Oestradiol-17\g=b\ failed to give the Kober colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1955
1955
1975
1975

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(16 citation statements)
references
References 1 publication
0
16
0
Order By: Relevance
“…The fluoacid and quinol concentrations in Kober's reagent, rescence of free oestriol, oestradiol, oestrone, and heating coil temperature, and final acid con centra-their monoglucuronides was measured relative to tions. Brown (1952) has shown that these factors this standard under differing conditions of acid affect both the colour and fluorescence produced and quinol concentration in Kober's reagent, heating by all the oestrogens and also that different oestro-coil temperature, and final acid concentration. A gens react in different ways to changes in these number of urines, including a pooled urine, with conditions.…”
mentioning
confidence: 99%
“…The fluoacid and quinol concentrations in Kober's reagent, rescence of free oestriol, oestradiol, oestrone, and heating coil temperature, and final acid con centra-their monoglucuronides was measured relative to tions. Brown (1952) has shown that these factors this standard under differing conditions of acid affect both the colour and fluorescence produced and quinol concentration in Kober's reagent, heating by all the oestrogens and also that different oestro-coil temperature, and final acid concentration. A gens react in different ways to changes in these number of urines, including a pooled urine, with conditions.…”
mentioning
confidence: 99%
“…An example of such an inhibitor is saccharolactone. (6) It is possible to separate saccharolactone from the estrogen glucuronosides in urine by gel-filtration. (7) It is likely that competitive substrates of either normal dietary or of therapeutic origin and saccharolactone account for much of the inhibition ob served on adding urine to ß-glucuronidase.…”
Section: Discussionmentioning
confidence: 99%
“…The extent of hy drolysis of phenolphthalein glucuronide and p-nitrophenyl glucuronide was determined by adding glycine buffer (pH 10-5) to an appropri ately diluted aliquot of the incubation medium and comparing the optical density at 545 and 395 mji,, respectively with previously determined standard curves for phenolphthalein and p-nitrophenol. The extent of hydrolysis of estradiol glucuronide (17 ß-monoglucuronide) and estriol glucuronide (principally the 16 a-glucuronide, but probably a mixture, of mono-and di-glucuronides, [7]) was deter mined by extracting the incubation media with ethyl acetate, evapo rating the solvent and applying the Kober reaction [6]. Pregnanediol was extracted with a mixture of benzene and ethyl acetate (6:4) and was determined by the procedure of Ronan et al [23].…”
Section: Effect Of Saccharolactone and The Concentration Of Enzyme Anmentioning
confidence: 99%
See 1 more Smart Citation
“…Brown 15 substituted hydroquinone for phenol to lessen the oxidation of the estriol fraction by the sulfuric acid. With this modification, the Kober method lacked maximum sensitivity because numerous impunttes in urine produce a yellow color in the Kober…”
Section: Urinary Estrogens As a Measure Of Fetoplacental Well-beingmentioning
confidence: 99%